Upaya Meningkatkan Kemampuan Pemahaman Konsep Matematika dengan Menggunakan Model Pembelajaran Kooperatif Tipe STAD - Siti Muthiah; Nurhasanah Siregar (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research was carried out in order to improve the Concept Understanding ability of students in class VII (1) MTsN 2 Medan at the 2023/2024 academic period using the STAD type cooperative learning model and to find out the answer mechanism for the students' Mathematical Concept Understanding ability test in the class listed. The method used is classroom action research with 2 cycles. The research subjects consisted of 29 students at level VII (1) MTsN 2 Medan. Data was collected through observation leaflets of teaching staff and students as well as mathematical concept ability tests. Passing the initial ability test scores, the points increased from the Mathematical Concept Understanding Test in cycle I, the average point was 44.82, compared to the second cycle, the average point was 86.19. So, the average increase in class size is 13.14. From the aspect of student learning completeness in cycle I, the number of students who completed learning was 13 out of 29 students or 44.82%, while the total number of students who achieved learning completeness in cycle II was 25 out of 29 students or 86.19%, so that it was achieved increase in students' ability to understand mathematical concepts by 27.78%. Likewise with the learning management carried out by teachers. In cycle I, the points obtained were 2.2 with a good level and in cycle II, the points obtained were 3.32 with a very good level. It can be concluded from the research results that the STAD Type Cooperative Learning Model can improve the ability to understand mathematical concepts by using the STAD Type Cooperative Learning Model in Class VII (1) MTsN 2 Medan.